The Analysis of the Determination of the Funding Bpbd Perdaerah using the Method of Mfep in West Sumatra - Nugraha Rahmansyah; Shary Armonitha Lusinia (Jurnal KomtekInfo, 2019)
A natural disaster is a disaster caused by event or series of events caused by nature, such as earthquakes, tsunamis, volcanic eruptions, floods, droughts, hurricanes, and landslides. In this case the action of handling and natural disaster management is the responsibility of the central government and local government. Data budget or funding indicative SKPD BPBD West Sumatra that has been composed must be as effective as possible in its distribution. With the use of information and communication technology can help in penentuaan funding in each area. This study analyzes the natural disasters that occurred in each region in West Sumatra to determine funding in tackling natural disasters. In this case, day this provide a solution to existing problems by creating a decision support system methods of Multifactor Evaluation Process (MFEP).